A Focus on Types of Compatible Mappings in \(S\)-metric Space - Vijayabaskerreddy, Bonuga; Rao, Ramachandruni Umamaheshwar (Communications in Mathematics and Applications, 2022)
In this article, we study unique common fixed point theorems for four self mappings in S-metric space using generalized concepts of compatible mappings such as compatible mappings of type (A), type (B) and type (C). Our results are generalizing the theorems proved by Sedghi et al. (Common fixed point of four maps in S-metric spaces, Mathematical Sciences 12 (2018), 137 – 143) in metric space.